Musical Genre Distinction and the Uniculture: A Reply to Simon Frith’s “Is Jazz Popular Music?” - Morse, Michael W. (Jazz Research Journal, 2008)
Simon Frith’s stimulating “Is Jazz Popular Music?” raises broader issues than the generic relations between these forms of musical experience. Even the specifically musical correlations transcend genre, involving the general history of dance energy. Moreover, both labels have comprised and designated very different musical experiences throughout their institutional, discursive, and social histories. These differences are reflected in the consistently contrasted perspectives of jazz and pop scholars, and by important shifts in the very definition of ‘music.’ In the contemporary context, jazz and popular music present contrasting but related faces in relation to the all-embracing uniculture of recent years.